Study of indicators of endothelial dysfunction in rats with experimental peritonitis - Gutsulyuk, V.; Savytskyi, I.; Tsypoviaz, S.; Znamerovskyi, S.; Sarahan, V.; Gerasymenko, T. (Journal of Education, Health and Sport, 2022)
The article presents the results of the study of the activity of endothelial and inducible NO-synthase, the level of Willebrand factor and endothelin-1 in rats with experimental peritonitis. The most likely mechanism that is damaged in the endothelium during peritonitis is the activation of the synthesis of inducible NO-synthase by neutrophils/macrophages in response to infection. It is possible that hyperproduction of nitric oxide (NO), on the one hand, is aimed at destroying microflora and oxidizing toxins, and on the other hand, at suppressing the expression of tissue factor and cell adhesion molecules. platelet aggregation and cascade disorders in the hemostasis system. All this indicates that the hyperproduction of NO not only reflects the processes that occur in the focus of damage to the vascular endothelium, but also affects the severity of the inflammatory process and the outcome of the disease. In animals with experimental peritonitis on the background of OS, an increase in the number of circulating desquamated endothelial cells in the blood, which is a highly specific marker of endothelial dysfunction, was noted. The level of the Willebrand factor also increased, which can serve as a marker of increased risk of thrombus formation and indicate the pathogenetic dependence of the factors that damage the vascular wall endothelium on the concentration of the Willebrand factor, which contributes to the reduction of vascular permeability by adhesion of platelets to the endothelium. Confirmation of the development of endothelial dysfunction in peritonitis is an increase in the concentration of endothelin-1, which is a regulator of the process of vascular neoangiogenesis in response to endothelial damage.